Unidad habitacional temporal flexible para familias en condición de calle (2023)
This research document - creation first of all addresses the problem of the precarious habitat of people who do not have access and quality housing, from different areas, being urban, social and spatial, dealing with vulnerable population living on the streets and without access of housing, in such a way that different architectural perspectives are implemented as alternative temporary housing development methods based on a spatial flexibility that provides adaptable areas based on Yona Friedman and the Metabolists, on a modifiable habitat architecture at the user's will and Shigeru Ban's spatial philosophy, among others, to propose a comprehensive housing project aimed at these people, where various residential guidelines and spatial configurations are taken into account for the integration of different groups of underprivileged families, thus being an architectural project with great social focus.